2007
DOI: 10.1118/1.2759839
|View full text |Cite|
|
Sign up to set email alerts
|

Out‐of‐field dose equivalents delivered by proton therapy of prostate cancer

Abstract: Measurements were performed to assess the dose equivalent outside a primary proton treatment field, using a silicon-on-insulator ͑SOI͒ microdosimeter. The SOI microdosimeter was placed on the surface of an anthropomorphic phantom and dose equivalents were determined as a function of lateral distance from a typical passively scattered and modulated prostate treatment field. Measurements were also completed within a polystyrene plate phantom as a function of depth for a distance of 5 cm from the field edge, as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 23 publications
(33 reference statements)
6
88
0
Order By: Relevance
“…6͑b͒. Wroe et al 36,33 measured the dose equivalent for prostate cancer and cranial medulloblastoma fields and their results are smaller by factors of 1-3 compared to Fig. 6.…”
Section: Ivb Neutron Contribution To the Total Dosementioning
confidence: 99%
See 1 more Smart Citation
“…6͑b͒. Wroe et al 36,33 measured the dose equivalent for prostate cancer and cranial medulloblastoma fields and their results are smaller by factors of 1-3 compared to Fig. 6.…”
Section: Ivb Neutron Contribution To the Total Dosementioning
confidence: 99%
“…Figure 6 shows the dose equivalent using average neutron weighting factor of 10, which is similar to the average used in measurements with passive scattering in many previous publications. 14,29,[33][34][35][36] We compare the simulated dose to other publications for further validation of the Monte Carlo model. Tayama et al 32 used a MLC, 16 cm range in water, and three MLC settings.…”
Section: Ivb Neutron Contribution To the Total Dosementioning
confidence: 99%
“…Active delivery techniques produce less neutrons out-of-field in comparison with passive delivery as has been demonstrated by Monte Carlo studies [82,83]. Dose equivalents out-of-field using SOI microdosimeters were measured within a polystyrene phantom for different clinical scenarios at the Loma Linda University Medical Centre (LLUMC) and Massachusetts General Hospital (MGH) proton therapy facilities [84,85]. Fig.…”
Section: Semiconductor Dosimetry For Dose Equivalent In Charged Partimentioning
confidence: 94%
“…This is in good agreement with the quality factor along the central axis for the beam block and downstream of the SOBP where only neutrons are presented. More detailed information on the dose equivalent and Q-factors measured by SOI microdosimeters in out-of-field proton therapy can be found in [84,85]. An advantage of SOI microdosimetry is the small physical size of the detector SV in comparison with most TEPC and Bonner spheres.…”
Section: Semiconductor Dosimetry For Dose Equivalent In Charged Partimentioning
confidence: 99%
“…The value decreased significantly with lower beam energy and increasing distance of fetus from the field edge. There are other studies of out‐of‐field secondary neutron both with Monte Carlo (MC) calculations or experimental measurements that could be used to estimate the neutron H to the fetus for passive scattering and uniform scanning beams 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 . However, most of these studies were made for a specific proton beam configuration, and the reported values of neutron H vary markedly because of different machine designs, experimental setups, and measurement instruments.…”
Section: Introductionmentioning
confidence: 99%